P61 Pulmonary nontuberculous mycobacterial (NTM) culture is common following lung transplantation, and NTM lung disease is associated with poor prognosis. (16th November 2010) - Gorsuch, T T; Crossingham, I; Cullen, M; Al-Aloul, M
Abstract : Introduction: NTM lung disease (NTMLD) is commonly associated with advanced pre-existing lung disease or defective cellular immunity. Lung transplant (LTx) recipients receive potent immunosuppression and often have structural lung abnormalities, so might be at uniquely high risk of NTM infection and disease. However, there is little published about NTM following LTx. Method: We carried out a retrospective study of NTM in LTx recipients attending our centre between 1/1/2005 and 31/8/2009. NTMLD was diagnosed according to American Thoracic Society (ATS) guidelines. Results: 326 respiratory samples (from 172 LTx recipients) were sent for mycobacterial culture, of which 51 samples (15.6%) from 39 patients (22.6%) grew NTM. Samples from 32 patients (82%) grew M avium complex (MAC), three grew M abscessus, two M gordonae, one M kansasii and one M malmoense . Nine patients had multiple positive cultures (maximum four), but only one species was ever isolated from each individual. None had NTM preoperatively, although one had a single isolate of NTM before the study period. 23 patients had positive culture from BAL or multiple sputum samples, and 21 patients had chest radiology compatible with NTM. ATS radiological and microbiological criteria were met in 13 patients (33%). Those diagnosed with NTMLD according to ATS guidelines had a significantly higher death rate than those from whom no NTM were isolated (HR 2.42, 95% CI 1.09 to 5.37), whereas those who did not meet ATS criteria did not. Four patients were treated for NTM: one was cured, while two deteriorated and died. The fourth developed renal impairment and treatment was abandoned; symptoms and lung function improved. Comment: In our cohort, respiratory NTM were cultured more frequently than previously reported, but a smaller proportion met ATS criteria for NTMLD and fewer were treated than in a previous cohort (15.6%, 33% and 10% respectively, compared with 6.5%, 73% and 82%). MAC is consistently the most common isolate. Patients with NTMLD by ATS criteria do worse than those without. Our data suggest that LTx is likely to be a risk factor for NTM infection but the majority of isolates represent colonisation/contamination. We advocate following ATS guidelines for treatment decisions of NTMLD after LTx.